Results of inverse dynamics calculations in javelin throwing are strongly influenced by individual body segment properties - Köhler, H.-P.; Schüler, A.; Roemer, K.; Witt, M. (ISBS Proceedings Archive (Michigan), 2021)
The calculation of inverse dynamics (ID) solutions is widely used to examine potential injury risks and sources for performance enhancement. The results of these calculations are influenced, among others, by the chosen set of body segment inertia parameters (BSIP). While throwing movements are frequently analyzed via ID and there exists a broad variety of BSIP models, the influence of the BSIP sets on the outcome is not well examined. Therefore, the aim of this study was to clarify the influence of different BSIP sets on the modelling results in javelin throwing. For this purpose the kinematics of ten male javelin throwers were recorded. Six available models were used to estimate the BSIP values of the upper limp for each thrower. The chosen BSIP model had large influence on the derived BSIP parameters which showed variations between 8% and 120%. Also, the maximum net joint moment varied between 6% and 21%. Hence, our study suggests that for modelling joint kinetics in throwing movements the model should be chosen carefully.